Social Status of Nepalese Single Women and Perception on Remarriage: A Case Study of Pokhara Lekhnath Metropolitan City - Tiwari, Surendra; Bhattarai, Sabitri (Journal of Development and Social Engineering, 2017)
The aim of this study is to examine the social status of Nepalese single women and their perception on remarriage. For this purpose, out of 157 respondents, 128 single women (7.3% margin of error and 90% Confidence level) of age 25 years to 80 years, from Pokhara Metropolitan City Ward No. 26 and 27 were interviewed purposively by using structured questionnaire. Descriptive statistics was used for the analysis of the data. Majority of single women were from age group of 40 years and above. Majority of them were illiterate and deprived from the political, social and economic participation. Major problems faced by the single women are economic hardship, family violence (especially mental tension given by the family and society), less freedom, deprivation of the social and economic rights and participations, less decision making roles and so on. Further, the majority of the single women had very little freedom to do something and go somewhere. It is also found that the land ownership has been transferred to them but it is due to legal provision after the death of husbands only. The result also shows that the single women faced the problem of loneliness. Majority of respondents think about remarriage without leaving children. It clearly shows that majority of the single women want to remarry not for physical pleasure but concerning about their safety, their children future and less economic burden. The study depicted that the barriers for the single women in social and religious participations have been changed slowly. It can be concluded that the social status of single women seems to be changing towards positive social status such as society has been liberal in their clothing and participation in various religious functions.